(untitled) (Journal of Economic Additions, 2020)
This study aimed to identify one of the modern trends in the economy namely as purple economy, which represents the way to value the cultural return of goods and services in order to pursuit the goals of a sustainable economy. Then, to define the relationship between the purple economy and corporate social responsibility, this is about institutions looking for a competitive advantage to achieve success and excellence in the field of business, all of this will only come through a flexible keeping up of the changes and modern trends that the economy is witnessing in our time, with a view to achieving sustainable performance and which will have a positive impact on sustainable development. Key words: Purple Economy; Corporate Social Responsibility; sustainable development. Jel Classification codes : Z19; M14.